Development of Simple Organ Pipe Learning Media with The Help of Sound Generator Software - Izza, Nur Imania; Sholihah , Bidadari; Nur Hanifah , Amelia; Raihanida Hakim , Marsa; Dewi , Shinta; Suryadi , Ahmad; Hernawati Husumah , Fuji (Jurnal Multidisiplin Indonesia, 2023)
This research is motivated by the process of making a simple resonant pipe tool in organa pipe practicum. The purpose of writing this research is to analyze the effect of frequency on the speed of propagation of sound using paralon and prove the experiment on the speed of propagation of sound. This research is done by experiment, where the pipe is inserted in a container in the form of a bucket filled with water, and the audio generator application is placed on the pipe until it produces the biggest sound with a certain tone which is done by raising the position of the pipe. The results of this study are organa pipe practicum using simple tools carried out by trials and obtained data on the speed of propagation generated at frequencies of 1400 Hz, 2000 Hz and 2600 Hz sequentially by 350 m/s, 360 m/s and 364 m/s. The research gives the result that f ~ v and the results show that the sound propagation speed data is close to 340 m/s. So it can be concluded that the frequency with the speed of propagation of sound is directly proportional through a simple organa pipe experiment, and the resulting propagation speed of both frequencies of 1400 Hz, 2000 Hz, and 2600 Hz around the original propagation speed of 340 m/s. Therefore, this organa pipe props can be called accurate and can be easier to use for students.